Risk of squamous cell skin cancer after organ transplant associated with antibodies to cutaneous papillomaviruses, polyomaviruses, and TMC6/8 (EVER1/2) variants. (10th June 2014) - Madeleine, Margaret M.; Carter, Joseph J.; Johnson, Lisa G.; Wipf, Gregory C.; Davis, Connie; Berg, Daniel; Nelson, Karen; Daling, Janet R.; Schwartz, Stephen M.; Galloway, Denise A.
Abstract Squamous cell skin cancer (SCSC) disproportionately affects organ transplant recipients, and may be related to increased viral replication in the setting of immune suppression. We conducted a nested case–control study among transplant recipients to determine whether SCSC is associated with antibodies to cutaneous human papillomaviruses (HPV), to genes associated with a rare genetic susceptibility to HPV (TMC6/TMC8), or to human polyomaviruses (HPyV). Cases (n = 149) had histologically confirmed SCSC, and controls (n = 290) were individually matched to cases on time since transplant, type of transplant, gender, and race. All subjects had serum drawn immediately prior to transplant surgery. Antibodies to 25 cutaneous HPVs and six HPyVs were assayed by detection of binding to virus‐like particles, and 11 TMC6/8 variants were genotyped. After correction for multiple comparisons, only antibodies to HPV37 were associated with SCSC (OR 2.0, 95% CI 1.2–3.4). Common genetic variants of TMC6/8 were not associated with SCSC, but three variants in TMC8 (rs12452890, rs412611, and rs7208422) were associated with greater seropositivity for species 2 betapapillomaviruses among controls. This study suggests that some betaHPVs, but not polyomaviruses, may play a role in the excess risk of SCSC among transplant recipients.